O show do Messias neoconservador: moralidades religiosas antigênero e entretenimento televisivo na construção do bolsonarismo - Pereira, Gisele Cristina (2022)
The present work has as its object the resonance of religious moral ideology and the discursive tools of the so-called anti-gender crusades in Bolsonaro's speeches, in television entertainment, between the years 2013 and 2018. The suspicion that gave rise to the research is that the religious moral discourse against gender, allied to the language of entertainment, contributed to the formatting and composition of what we understand today by Bolsonarism. The research is part of the intersection between gender, politics and religion. From the Science of Religion and theoretical references of feminism, we seek to understand the role played by neoconservative sexual morality in the constitution of Bolsonarism and how this moral is articulated with other components of Bolsonarism and with the mediatization process, investigating precedents, context , articulations and internal dynamics of the functioning of this phenomenon. For this, we pursue Bolsonaro's trajectory in three ways: the first, through the historical and economic context that makes it possible, as well as the movements and actors that shape and precede it; the second, for his political trajectory and his approach to the anti-gender agenda; the third, through the analysis of his speech in entertainment programs